2019
DOI: 10.1111/jcmm.14785
|View full text |Cite
|
Sign up to set email alerts
|

α‐Mangostin suppresses the de novo lipogenesis and enhances the chemotherapeutic response to gemcitabine in gallbladder carcinoma cells via targeting the AMPK/SREBP1 cascades

Abstract: High rates of de novo lipid synthesis have been discovered in certain kinds of tumours, including gallbladder cancer (GBC). Unlike several other tumours, GBC is highly insensitive to standard adjuvant therapy, which makes its treatment even more challenging. Although several potential targets and signalling pathways underlying GBC chemoresistance have been revealed, the precise mechanisms are still elusive. In this study, we found that α‐Mangostin, as a dietary xanthone, repressed the proliferation and clone f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Student's t-test was used to analyse the comparison between two groups. 34 One-way ANOVA followed by Dunnett's test in GraphPad Prism version 5 (GraphPad Software, San Diego, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Student's t-test was used to analyse the comparison between two groups. 34 One-way ANOVA followed by Dunnett's test in GraphPad Prism version 5 (GraphPad Software, San Diego, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins in conditioned medium were extracted as previously described [ 19 ]. Western blot assays and densitometric analysis of the resulting protein bands were performed as previously described [ 19 , 20 ]. For co-IP assays, GBC cells were lysed with lysis buffer, and the protein concentration of the cell lysates was determined by BCA quantitation.…”
Section: Methodsmentioning
confidence: 99%
“…27,28 α-M could enhance the chemotherapeutic response in gallbladder carcinoma cells. 29 Next, the mechanism by which α-M could trigger autophagy to enhance the chemosensitivity of GC cells was investigated. A previous investigation revealed that aberrant STAT3 expression is associated with neoplastic growth, metastasis, and prognosis; it is also involved in autophagic regulation, which may in turn contribute to tumor chemoresistance.…”
Section: Discussionmentioning
confidence: 99%